Synchronization method for long-term evolution-based machine-type communication in low-power cellular Internet of Things. (August 2016) - Pec, Rothna; Choi, Joo-Hyung; Park, Chang-Hwan; Cho, Yong Soo
The significant growth of machine-to-machine applications for low-power cellular Internet of Things has compelled 3rd Generation Partnership Project to ensure that the future release of long-term evolution can support massive transfer of small, infrequent packets using ultra-low-power and low-cost devices. The 3rd Generation Partnership Project version of machine-to-machine, called "machine-type communication, " is currently being standardized for low-cost machine-type communication operations. In this article, a complete synchronization and cell search procedure is described for machine-type communication devices in long-term evolution systems. Low-complexity algorithms for primary synchronization signal and secondary synchronization signal detection, which requires the highest computational complexity in synchronization and cell search period, are also proposed for low-power machine-type communication devices. Through simulation under long-term evolution-based machine-type communication environments, we show that the proposed methods for primary synchronization signal and secondary synchronization signal detection require six and five times less computational complexity than the conventional methods, respectively, while their performance is similar. The proposed algorithms allow machine-type communication devices in a discontinuous reception cycle to resynchronize quickly with less power when synchronization is lost during a deep sleep period.